2015
DOI: 10.1007/s10592-015-0758-5
|View full text |Cite
|
Sign up to set email alerts
|

Effective number of breeders in relation to census size as management tools for Atlantic salmon conservation in a context of stocked populations

Abstract: Monitoring short-term fluctuations in effective population sizes (N e ) and effective number of breeders (N b ), as well as their ratio to adult census population size (N e /N c and N b /N c ), provide insight into population demography and inform conservation programs towards limiting long-term loss of evolutionary potential in wild populations. In this study, we monitored short-term variations of N b and N b /N c over three consecutive years for nine Atlantic salmon populations from Quebec, Canada. We docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 72 publications
(125 reference statements)
6
30
0
Order By: Relevance
“…For population monitoring purposes, either in the context of a LITS or for point evaluation of management practices, comparison of N b estimates through time and space [control v . treatment comparison (Ozerov et al, )] or between populations [evaluating the effect of stocking (Perrier et al, )], several factors should be considered during sampling design as demonstrated herein. First, sampling time of year should be the same across years and populations, because it is sensitive to time of sampling as N b accounts for YOY survival until sampling.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…For population monitoring purposes, either in the context of a LITS or for point evaluation of management practices, comparison of N b estimates through time and space [control v . treatment comparison (Ozerov et al, )] or between populations [evaluating the effect of stocking (Perrier et al, )], several factors should be considered during sampling design as demonstrated herein. First, sampling time of year should be the same across years and populations, because it is sensitive to time of sampling as N b accounts for YOY survival until sampling.…”
Section: Discussionsupporting
confidence: 79%
“…There was no significant correlation between N b and N c across 10 years in the River Nivelle. Indeed, N b and N c did not co‐vary across years leading to high inter‐annual variation of N b : N c as previously reported for the species (Palstra et al, ; Ferchaud et al, ; Perrier et al, ). This typical variation in N b : N c in combination with lack of correlation between N b and N c may indicate that variance in reproductive success could be an important factor in N b variation in this population, in addition to the number of individuals that effectively reproduced (Luikart et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R. Soc. B 283: 20152601 phenomenon and is a function of variation in the effective number of breeders (see also [14,39,43]) and in reproductive success. In fact, given the estimated age-specific survival rates and age-or size-specific relative frequencies, we have shown with AGENE [34] that very high variances in reproductive success (between 50 and 100 times higher than the mean reproductive success) are necessary to generateN e =N c in the 0.05-0.02 range (200 times higher to generate ratios % 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…They attributed this to decreased variance in reproductive success at small population sizes ( see also Hedrick ; Perrier et al. ) and suggested several biological explanations, such as higher fraction of reproducing individuals in small populations, a decrease in competition for mates or a decrease in embryo mortality. In the current study, neither annual nor lifetime variance in reproductive success decreased as N decreased.…”
Section: Discussionmentioning
confidence: 99%